Interface shear strength testing method
By using hollow circle table with inclination angle as a maintenance device in the interface shear strength test, the problems of high data discreteness and poor repeatability in the existing test methods are solved, and higher reliability and accuracy of test results are achieved.
Patent Information
- Application Number
- CN202311377483.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-10-23
AI Technical Summary
The existing interface shear strength testing methods have the problems of high data discreteness and poor repeatability, and are greatly affected by the mold processing accuracy, resulting in large experimental errors.
An interface shear strength testing method is used to create a hollow circle with a preset inclination angle with the horizontal plane as a maintenance device, and a certain angle is formed between the simulated interface and the load to reduce the impact of friction on the measurement results.
By reducing data discretism and improving the reliability of test results, the interface cementation can be more accurately reflected, and the accuracy and repeatability of the experiment can be improved.
Smart Images

Figure CN119880654A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cementing engineering for oil and gas drilling operations, and in particular to a method for testing interface shear strength. Background Art
[0002] Cementing engineering is an important part of oil and gas drilling and completion engineering. The quality of the interface bonding between the cement sheath, casing and formation is a key factor affecting the cementing quality of oil and gas wells, and determines the interlayer isolation capacity of oil and gas wells throughout their life cycle. Good bonding quality can reduce the formation of micro-annulus at the interface, prevent the formation fluid from flowing along the interface, and avoid safety accidents such as blowouts.
[0003] Among the common interface bonding failure forms in underground wells, shear failure is a common situation, which is usually caused by relative slip between the cement sheath and the casing or formation under the influence of complex load changes under high temperature and high pressure environment. Therefore, the interface shear strength is an important indicator for evaluating the interface bonding performance. At present, the common method for testing interface shear strength is the "extrusion method", that is, a cylindrical simulated core or cement stone is maintained in the center of the mold, and a vertical load is applied to the simulated core or cement stone to make it detach from the cement-core or cement-casing interface. The shear strength value can be obtained by dividing the load at this time by the contact area (Lu Chenghui, Wang Jie, Yang Qingjiang, et al. Cementing interface bonding strength test device [P]. Beijing: CN205280557U, 2016-06-01.). However, this method has certain limitations, that is, during the process of applying the load, the friction between the interfaces will cause great errors in the measurement results, resulting in high discreteness and poor repeatability of the obtained data. In addition, this type of evaluation method is greatly affected by the mold processing accuracy. The uneven inner diameter of the mold will further amplify the experimental error and even cause the body of the sample to be damaged during the load process. Summary of the invention
[0004] In view of this, the present invention proposes a method for testing interface shear strength, comprising the following steps:
[0005] Step 1: Making a curing device: making a hollow truncated cone with a preset inclination angle θ with the horizontal plane as the curing device;
[0006] Step 2: Assembly production: fix the curing device upside down on the first plate, pour the prepared cement slurry into the cavity of the curing device until it overflows, place the second plate on top for compaction, cure and shape in a high temperature and high pressure environment, and then remove the first plate and the second plate to obtain the assembly;
[0007] Step 3: Pressure test: place the assembly on a fixing device, place the pressure head coaxially on the top surface of the curing device, and start the pressure test device to measure the interface shear strength.
[0008] Furthermore, the calculation formula of the interface shear strength is:
[0009] Wherein, P is the interface shear strength, MPa; F is the failure load, kN; θ is the inclination angle of the curing device; h is the height of the curing device, mm; d is the inner diameter of the top surface of the curing device, mm; and D is the inner diameter of the bottom surface of the curing device, mm.
[0010] Furthermore, the operation methods of steps one to three are used to test the shear strength of the first interface and the second interface.
[0011] Furthermore, the first flat plate and the second flat plate are both flat and smooth stainless steel plates.
[0012] Furthermore, when the maintenance device is placed on the first flat plate, a thin layer of sealing grease is applied on the contact surface.
[0013] Furthermore, the inclination angle θ is greater than 40° and less than 90°.
[0014] Furthermore, the maintenance device used for the interface shear strength test is made of stainless steel.
[0015] Furthermore, the maintenance device used for the two-interface shear strength test is made of rock.
[0016] Furthermore, the inclination angle θ is preferably 50°, 60°, 70°, or 80°.
[0017] The interface shear strength test method provided by the present invention is improved on the classic "extrusion method" so that a certain angle is formed between the simulated interface and the load during the test process, thereby avoiding errors in the experimental results caused by factors such as the friction between the mold and the sample and the mold processing accuracy during the shear failure of the interface, reducing data discreteness, and improving the reliability of the test results. At the same time, it is beneficial to further analyze the sample after demolding; it can also switch between the first and second interface simulation experiments by switching the material of the curing device, and has good applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0019] Figure 1 A schematic diagram of the steps of the interface shear strength testing method provided by an embodiment of the present invention;
[0020] Figure 2A schematic diagram of the interface shear strength testing device provided in an embodiment of the present invention;
[0021] Figure 3 The state of cement stone released after testing in an interface experiment provided by an embodiment of the present invention;
[0022] Figure 4 The state of the cement stone released after the test in the two-interface experiment provided in the embodiment of the present invention;
[0023] 1. Pressure head, 2. Maintenance device, 3. Fixing device, 4. Pressure testing device. DETAILED DESCRIPTION
[0024] Exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to be able to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features described in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0025] See also Figure 1 As shown, it is an interface shear strength test method provided by an embodiment of the present invention, comprising the following steps: step one, preparation of a curing device, preparing a hollow truncated cone with a preset inclination angle θ with the horizontal plane as the curing device; step two, preparation of an assembly, fixing the curing device upside down on a first flat plate, pouring the configured cement slurry into the cavity of the curing device until it overflows, placing a second flat plate on top for compaction, curing and forming in a high temperature and high pressure environment, and then removing the first and second flat plates to obtain an assembly; step three, pressure testing, placing the assembly on a fixing device, placing the pressure head coaxially on the top surface of the curing device, and starting the pressure testing device to measure the interface shear strength.
[0026] In this embodiment, the calculation formula of the interface shear strength is:
[0027] Wherein, P is the interface shear strength, MPa; F is the failure load, kN; θ is the inclination angle of the curing device; h is the height of the curing device, mm; d is the inner diameter of the top surface of the curing device, mm; and D is the inner diameter of the bottom surface of the curing device, mm.
[0028] In this embodiment, the operating methods of steps one to three are used to test the shear strength of the first interface and the second interface. The first plate and the second plate are both flat and smooth stainless steel plates. When the maintenance device is placed on the first plate, a thin layer of sealing grease is applied to the contact surface. The inclination angle θ is greater than 40° and less than 90°. The maintenance device used for the shear strength test of the first interface is made of stainless steel. The maintenance device used for the shear strength test of the second interface is made of rock. The inclination angle θ is preferably 50°, 60°, 70°, or 80°.
[0029] The specific example of using the above-mentioned interface shear strength test method to test an interface shear strength is as follows: Example 1
[0030] (1) A hollow truncated cone with a preset tilt angle θ of 80° with the horizontal plane is made of stainless steel as a maintenance device;
[0031] (2) Preparation of cement slurry: Cement slurry was prepared according to GB / T 19139-2012 standard, and the shear strength performance test was carried out by simulating the cement sheath interface; the cement slurry formula was as follows: Jiahua G-grade oil well cement 100g + fluid loss reducer BXF-200L (AF) 4g + retarder BXR-200L 0.2g + fresh water 40g + defoamer G603 0.5g;
[0032] (3) Fix the curing device with the busbar inclined at an angle of 80° to the horizontal plane upside down on a flat and smooth stainless steel plate, and apply a thin layer of sealing grease on the contact surface between the curing device and the stainless steel plate; pour the prepared cement slurry into the cavity of the curing device until it overflows, place another stainless steel plate on top for compaction, and place the assembly in a water bath at 20 MPa and 80°C for curing for 3 days until it is cured and formed;
[0033] (4) Take out the assembly from the curing kettle, remove the stainless steel plate, place the curing device upright on the fixing device, place the pressure head coaxially on the top surface of the curing device, and use the pressure test device to measure the load required when the cement stone and the curing device slip relative to each other. Figure 2 The interface shear strength is calculated using the following formula:
[0034]
[0035] Wherein, P is the interface shear strength, MPa; F is the breaking load, kN; θ is the inclination angle of the curing device; h is the height of the curing device, mm; d is the inner diameter of the top surface of the curing device, mm; D is the inner diameter of the bottom surface of the curing device, mm; In this embodiment, the specific parameters of the curing device are consistent with the parameters used in the conventional "extrusion method", except that the inclination angle θ is set, which is no longer disclosed here. The final results of the tested interface shear strength are specifically shown in Table 1.
[0036] (5) Four groups of curing devices were set up, and each group was tested 5 times. The specific shear strength test results are shown in Figure 1.
[0037] Example 2
[0038] A hollow truncated cone with an inclined angle θ of 70° was used as the curing device. The same experiment was carried out according to the method of Example 1. The specific shear strength test results are shown in Table 1.
[0039] Example 3
[0040] A hollow truncated cone with an inclined angle θ of 60° was used as the curing device. The same experiment was carried out according to the method of Example 1. The specific shear strength test results are shown in Table 1.
[0041] Example 4
[0042] A hollow truncated cone with an inclined angle θ of 50° was used as the curing device. The same experiment was carried out according to the method of Example 1. The specific shear strength test results are shown in Table 1.
[0043] Comparative Example 1
[0044] A hollow truncated cone with an inclined angle θ of 90° was used as the curing device. The same experiment was carried out according to the method of Example 1. The specific shear strength test results are shown in Table 1.
[0045] Comparative Example 2
[0046] A hollow truncated cone with an inclined angle θ of 40° was used as the curing device. The same experiment was carried out according to the method of Example 1. The specific shear strength test results are shown in Table 1.
[0047] Table 1 - Interface shear strength test results
[0048]
[0049] The above experimental examples and comparative examples all use a stainless steel curing device to simulate an interface. As shown in Table 1, compared with comparative example 1 (θ=90°), the curing device busbars designed in embodiments 1 to 4 (θ=80° to 50°) have a gradually decreasing angle θ between the horizontal plane and the curing device busbars. At this time, the angle between the simulated interface and the load gradually increases, and the interface shear strength value measured for the same cement slurry formula is significantly reduced. At the same time, the standard deviation of the measurement results also decreases, indicating that the design with a reduced angle θ significantly reduces the influence of the interface friction on the measurement results. While the measurement results tend to the true value, the measurement accuracy and repeatability are significantly improved. This can also be seen from the state of the cement stone being removed. Figure 3As shown, the cement stone in comparative example 1 is difficult to maintain a complete shape due to the friction of the interface, while all the cement stones in embodiments 1 to 4 are intact, and the damage only occurs at the interface. When the tilt angle θ is reduced to a certain extent, such as comparative example 2 (θ = 40°), the cement stone that has been released will be damaged in its entirety. This is because the damage at the interface is discontinuous and becomes a process close to "tearing". Therefore, the tilt angle θ needs to be controlled within a certain range. In this embodiment, the tilt angle θ is controlled within a range of greater than 40° and less than 90° to ensure the experimental effect.
[0050] The specific example of using the above-mentioned interface shear strength test method to test the two-interface shear strength is as follows: Example 1
[0051] (1) A hollow truncated cone with a preset tilt angle θ of 80° with the horizontal plane is made of rock as a curing device. In this embodiment, the rock material is selected to simulate the two interfaces, which can well perform the two-interface shear strength test;
[0052] (2) Preparation of cement slurry: Cement slurry was prepared according to GB / T 19139-2012 standard, and the shear strength performance test was carried out by simulating the cement ring interface; the cement slurry formula was as follows: Jiahua G-grade oil well cement 100g + fluid loss reducer BXF-200L (AF) 4g + retarder BXR-200L 0.2g + fresh water 40g + defoamer G603 0.5g;
[0053] (3) Fix the curing device with the busbar inclined at an angle of 80° to the horizontal plane upside down on a flat and smooth stainless steel plate, and apply a thin layer of sealing grease on the contact surface between the curing device and the stainless steel plate; pour the prepared cement slurry into the cavity of the curing device until it overflows, place another stainless steel plate on top for compaction, and place the assembly in a water bath at 20 MPa and 80°C for curing for 3 days until it is cured and formed;
[0054] (4) Take out the assembly from the curing kettle, remove the stainless steel plate, place the curing device upright on the fixing device, place the pressure head coaxially on the top surface of the curing device, and use the pressure test device to measure the load required when the cement stone and the curing device slip relative to each other. Figure 2 The operation method shown is used, and the interface shear strength is calculated by the following formula:
[0055]
[0056] Wherein, P is the interface shear strength, MPa; F is the breaking load, kN; θ is the tilt angle of the curing device; h is the height of the curing device, mm; d is the inner diameter of the top surface of the curing device, mm; D is the inner diameter of the bottom surface of the curing device, mm; In this embodiment, the specific parameters of the curing device are consistent with those used in the conventional "extrusion method", except that the tilt angle θ is set, which is no longer disclosed here. The final results of the tested interface shear strength are specifically shown in Table 1;
[0057] (5) Four groups of curing devices were set up, and each group was tested 5 times. The specific shear strength test results are shown in Figure 1.
[0058] Example 2
[0059] A hollow truncated cone with an inclined angle θ of 70° was used as the curing device. The same experiment was carried out according to the method of Example 1. The specific shear strength test results are shown in Table 1.
[0060] Example 3
[0061] A hollow truncated cone with an inclined angle θ of 60° was used as the curing device. The same experiment was carried out according to the method of Example 1. The specific shear strength test results are shown in Table 1.
[0062] Example 4
[0063] A hollow truncated cone with an inclined angle θ of 50° was used as the curing device. The same experiment was carried out according to the method of Example 1. The specific shear strength test results are shown in Table 1.
[0064] Comparative Example 1
[0065] A hollow truncated cone with an inclined angle θ of 90° was used as the curing device. The same experiment was carried out according to the method of Example 1. The specific shear strength test results are shown in Table 1.
[0066] Comparative Example 2
[0067] A hollow truncated cone with an inclined angle θ of 40° was used as the curing device. The same experiment was carried out according to the method of Example 1. The specific shear strength test results are shown in Table 1.
[0068] Table 2 Test results of two-interface shear strength
[0069]
[0070] In the simulation experiment of the shear strength of the second interface, the same test method and data parameters as those of the first interface were used. As shown in Table 2, in the experiment of the second interface, similar experimental results appeared as those of the first interface. In the test experiment of the second interface, as the angle θ between the designed curing device busbar and the horizontal plane gradually decreased, the angle between the simulated interface and the load gradually increased, and the interface shear strength value measured with the same cement slurry formula decreased significantly, and the standard deviation of the measurement results also decreased. This shows that the design of reducing the inclination angle θ significantly reduced the influence of the interface friction on the measurement results. While the measurement results tend to the true value, the measurement accuracy and repeatability are significantly improved. The experimental results can also be seen from the state of the cement stone, such as Figure 4 As shown, the cement stone that comes out of Comparative Example 1 of the two interfaces is difficult to maintain a complete shape due to the influence of the interface friction force, while all the cement stones that come out of Examples 1 to 4 are complete cement stones, and the damage only occurs at the interface, which is completely consistent with the results in the one-interface experiment. When the tilt angle θ is reduced to a certain extent, such as Comparative Example 2 (θ = 40°), the cement stone that comes out will undergo body damage. This is because the damage at the interface is discontinuous at this time and becomes a process close to "tearing". Therefore, the tilt angle θ needs to be controlled within a certain range. In this embodiment, the tilt angle θ is also preferably controlled within a range of greater than 40° and less than 90° to ensure the experimental effect. It can be seen that the shear strength test results of the two interfaces show a similar trend of change to that of the one interface. The interface shear strength test method provided in this embodiment is also applicable to the shear strength measurement of the one and two interfaces.
[0071] The interface shear strength test method provided by the embodiment of the present invention has the following advantages: it is improved on the classic "extrusion method" so that a certain angle is formed between the simulated interface and the load during the test process, thereby avoiding errors in the experimental results caused by factors such as the friction between the mold and the sample and the mold processing accuracy during the shear failure of the interface, reducing data discreteness, improving the reliability of the test results, and being able to reflect the interface bonding conditions; the interface shear strength test evaluation method is simple to operate and sample preparation, and the conversion between the first and second interface simulations can be achieved by replacing the material of the curing device from stainless steel to rock. At the same time, the curing device is small in size, and is combined with equipment such as a curing kettle to easily simulate underground high temperature and high pressure conditions. At the same time, large-scale batch curing can be carried out, which is convenient for control group comparison experiments.
[0072] It should be noted that, in the description of the present invention, terms such as "up", "down", "left", "right", "inside" and "outside" indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings. This is merely for the convenience of description and does not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation on the present invention.
[0073] In addition, it should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two components. For those skilled in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0074] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for testing interface shear strength, characterized in that: The steps include: Step 1: Making a curing device: making a hollow truncated cone with a preset inclination angle θ with the horizontal plane as the curing device; Step 2: Assembly production: fix the curing device upside down on the first plate, pour the prepared cement slurry into the cavity of the curing device until it overflows, place the second plate on top for compaction, cure and shape in a high temperature and high pressure environment, and then remove the first plate and the second plate to obtain the assembly; Step 3: Pressure test: place the assembly on a fixing device, place the pressure head coaxially on the top surface of the curing device, and start the pressure test device to measure the interface shear strength.
2. The interface shear strength testing method according to claim 1, characterized in that: The calculation formula of the interface shear strength is: Wherein, P is the interface shear strength, MPa; F is the failure load, kN; θ is the inclination angle of the curing device; h is the height of the curing device, mm; d is the inner diameter of the top surface of the curing device, mm; and D is the inner diameter of the bottom surface of the curing device, mm.
3. The interface shear strength testing method according to claim 1, characterized in that: The operation methods of steps 1 to 3 are used to test the shear strength of the first interface and the second interface.
4. The interface shear strength testing method according to claim 1, characterized in that: The first flat plate and the second flat plate are both flat and smooth stainless steel plates.
5. The interface shear strength testing method according to claim 1, characterized in that: When the maintenance device is placed on the first flat plate, a thin layer of sealing grease is applied on the contact surface.
6. The method for testing the interface shear strength according to claim 1, characterized in that: The inclination angle θ is greater than 40° and less than 90°.
7. The interface shear strength testing method according to claim 3, characterized in that: The maintenance device used for the interface shear strength test is made of stainless steel.
8. The method for testing interface shear strength according to claim 3, characterized in that: The maintenance device used for the two-interface shear strength test is made of rock.
9. The method for testing the interface shear strength according to claim 6, characterized in that: The inclination angle θ is preferably 50°, 60°, 70°, or 80°.
Citation Information
Patent Citations
Well cementation interface cementing strength testing arrangement
CN205280557U
Cementing strength testing device of oil well cement
CN105422080A
Three-way loading mine drilling and sealing effect simulation test device and method
CN111271051A
Method and system for evaluating cementation quality of two interfaces of high-temperature well cementation cement sheath
CN114626697A
Device, system and method for measuring consolidation strength of adhesion interface
CN116577269A